Risk sharing in finance : the Islamic finance alternative - Askari, Hossein (Wiley finance series, 2012)
The financial crisis of 2008 has motivated a number of academics, practitioners and policymakers to question the fundamental stability of the conventional financial system, a system predominantly based on debt financing and leveraging; with the embedded risk that the temptation of leveraging could become excessive, and this combined with the inherent asset-liability mismatch threatens the solvency of financial institutions and overall financial stability. An alternative to the conventional financial system is a system with no debt financing, only equity or direct asset financing; where there would be no "risk shifting" as happens with debt, only "risk sharing" as happens with equity or asset-financing. Financial institutions would be serving their traditional role as intermediaries between savers and investors but with no debt on their balance sheets, no opportunity to engage in leveraging and no predetermined interest rate payments as liabilities. Such a system has been suggested by a number of noted conventional economists over the last hundred years and it is the system whose basic principles have been advocated by Islam and to some extent by other Abrahamic religions. While a number of indicators point to rapid growth in the practice of Islamic finance, much of this growth, to our mind, has been superficial. Instead of developing a risk-sharing-friendly financial system, the practice of Islamic finance has become misaligned to replicating conventional finance. In this volume, the authors make an important attempt to develop the building blocks of an Islamic financial system and elaborate on its implementation as a comprehensive system. They make a convincing case for the world to shed its reliance on debt, interest and leveraging, and revamp the global financial system to rely more heavily on equity financing, genuine asset securitization linking the payoffs of financial securities to the underlying assets, and thus promoting wider risk sharing. --- Inside Flap